Combustion characteristics of colloidal droplets of jet fuel and carbon based nanoparticles. (15th January 2017) - Ghamari, Mohsen; Ratner, Albert
Abstract: Addition of micro and nano-sized particles to liquid fuels has proven to be a successful mechanism to improve certain combustion characteristics such as burning rate and ignition delay. In this study, sub-millimeter size droplets of colloidal suspensions of jet fuel and different types of carbon based nanoparticles were ignited and burned at ambient conditions to investigate the effects of particle size and morphology on combustion behavior. Carbon nanoparticles, nanotubes, and nanoplatelets with dimensions in the range of 2–3 nm to 100 nm were added to jet fuel at a wide range of mass concentrations. In general, higher burning rate (7–10% increase) was achieved for all of the carbon additives but it was found that the size and morphology of nanoparticles play an important role in the extent of this increase. For each particle type, a concentration was found at which maximum burning rate was achieved. It was observed that addition of more particle beyond this concentration would result in a burning rate reduction possibly due to the formation of large aggregates. Among the three carbon additives, nanotubes resulted in the highest burning rate increase at only 0.25% particle loading. Improved thermal and optical properties of these suspensions is believed to result in improved heat transfer within the droplet and an increase in the droplet temperature and evaporation rate.